Analisis Break Even Point sebagai Perencanaan Laba Jangka Pendek pada UMKM - AMANDA, FARIKA; Sandrayati; Evada Dewata (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2024)
This final report entitled, “Break Even Point Analysis as Short Term Profit Planningfor UMKM ASO," was prepared to complete Diploma III education in the Accounting Department at the Sriwijaya State Polytechnic. The data used to analyze Break Even Point (BEP) includes sales recapitulation, raw material costs, and price data for the first three years of production, namely 2021, 2022, and 2023. Based on the information and data obtained, it is concluded that UMKM ASO have not grouped costs allocated into fixed costs and variable costs. As a result, the company is unable to reach the break-even point and Margin of Safety (MoS) which is needed as a tool in making the right decisions for the company's future development.